ANALYSIS OF INACCURACIES IN THE PREPARATION OF THE PLAN FOR HYPERTENSION DRUG NEEDS OF THE NEW SELAT HEALTH CENTER - Rika Media Elona; Budi Hartono; Asmala Sari (HEARTY, 2026)
Accurate drug needs planning is an important component in ensuring the continuity of hypertension therapy as a chronic disease with high prevalence. However, the UPT Puskesmas Selat Baru still faces inaccuracies in the preparation of the Drug Needs Plan (RKO), which is marked by the occurrence of 27 incidents of stock-out of antihypertensive drugs and stock accumulation that causes expired drugs and state losses. This study aims to analyze the root causes of RKO inaccuracies and formulate alternative data-driven solutions to improve the effectiveness of drug management. The research uses a qualitative approach with a case study design through in-depth interviews, observations, and document review on purposively selected informants, including the Head of the Health Center, the Pharmacist in Charge, the Person in Charge of the P2PTM Program, and the Regency IFLK Pharmacist. Data validity is obtained through triangulation of sources, methods, and data. The analysis is carried out using the problem solving cycle and Fishbone Analysis to identify the main cause of the problem. The results of the study showed that the inaccuracy of planning was caused by the use of historical consumption methods without considering epidemiological trends, manual stock recording, low data accuracy, and low competence of officers in disease-based forecasting. The consequences are the instability of the availability of drugs, the non-achievement of Hypertension SPM, and budget losses. The study concluded that increasing human resource capacity through technical training "Epidemiology-Based RKO Management" is the most effective solution to improve planning accuracy and prevent recurrence of drug availability problems.